'In a partisan way': Želimir Žilnik's Uprising in Jazak and the reconstruction of antifascist memory from below. Issue 3 (15th July 2022) - Kirn, Gal
Abstract: This text works at the intersection of film, memory and politics taking the case of Želimir Žilnik's short film »Uprising in Jazak« (1973) as its object of study. Most notably, the text will present visual and alternative memory strategies. The text argues that Žilnik's film is one of the most prolific examples of making a partisan film in a partisan way from the epoch of socialist Yugoslavia. The film's raw image and cutting is a conscious politico-aesthetical intervention into the dominant genre of that time in socialist Yugoslavia – huge war partisan spectacles also called »Red Westerns«. Žilnik's method consists of a delicate bottom up ethnographic reconstruction of partisan and antifascist memory of the poor villagers in Vojvodina (village Jazak) who − 30 years after the war – collectively tell and renegotiate the stories of the antifascist resistance from the war. The visual language and method of Žilnik stays immensely actual today in post-socialist times of historical revisionism, also in terms of political message. Žilnik succeeds In complementing an Arendtian trope that analysed fascist collaboration from below in terms of »banality of evil« with something I name the everyday deeds and practices of resistances that constituted the partisan community.